Revision of the Caraphiini, New Tribe (Coleoptera, Cerambycidae, Lepturinae) - Ohbayashi, Nobuo; Lin, Mei-Ying; Yamasako, Junsuke (Zootaxa, 2016)
Caraphiini N. Ohbayashi, Lin & Yamasako, trib. nov. of the subfamily Lepturinae is erected for the genus Caraphia Gahan, 1906. The Central American genus Noctileptura Chemsak & Linsley, 1984 is synonymized with the southeast Asian genus Caraphia. Caraphia huai N. Ohbayashi & Lin, sp. nov., from Hainan and Guangdong, China, Caraphia paulastoni N. Ohbayashi & Lin, sp. nov. from Hong Kong, China and Caraphia lingafelteri N. Ohbayashi & Yamasako, sp. nov. from Matagalpa, Nicaragua are described. All the known sixteen species of the newly defined genus Caraphia are revised with a key and their habitus.